QUALITY OF LIFE OF PATIENTS AFTER TOTAL KNEE ARTHROPLASTY - Music Kenan; Pelicic Damir; Konatar Ranka; Maras Borko (Sanamed)
Introduction: Diseases of the musculoskeletal system are common in the general population. They significantly contribute to increased morbidity, more frequent use of healthcare services, reduced working capacity, increased professional absences, and the occurrence of disability.